Transcriptome-wide identification and characterization of toll-like receptors response to Vibrio anguillarum infection in Manila clam (Ruditapes philippinarum). Issue 111 (April 2021) - Ren, Yipeng; Liu, Huaxi; Fu, Siying; Dong, Wenhao; Pan, Baoping; Bu, Wenjun
Abstract: The Manila clam ( Ruditapes philippinarum ), one of the major marine aquaculture species in China, is susceptible to infection with the pathogen Vibrio, which results in massive mortality and economic losses. Toll-like receptors (TLRs) are significant pattern recognition receptors (PRRs) of innate immunity that are involved in immune regulation against pathogenic invasion. Molecular characterization of Manila clam TLRs and investigations of their immune functions are essential to prevent and control Vibrio infection. In the present research, eight cDNA sequences of R. philippinarum TLRs (RpTLRs) were identified from previous transcriptome libraries and then classified into four groups, namely, P-TLR (one sequence), V-TLR (one sequence), Ls-TLR (two sequences) and sP-TLR (four sequences), based on the corresponding LRR domain arrangement of their protein structures within the typical TLR motifs. A selective pressure test firstly suggested that the molluscan P-TLR, V-TLR, Ls-TLR and sP-TLR families underwent positive selection, and different numbers of positive selection sites (PSSs) were identified in different domains of the four types of RpTLRs, as determined by PAML and analysis of website data. These findings indicated that the evolution of RpTLRs may be associated with their immune recognition and function. Furthermore, tissue-specific expression analysis showed that all RpTLRs were ubiquitously expressed in all test tissues and were dominant in hemocytes. Quantitative real-time PCR revealed that the cDNA expression of all eight RpTLRs was upregulated after injection with Vibrio anguillarum ( P  < 0.01) in R. philippinarum hemocytes, revealing that these RpTLRs play important roles in responding to pathogenic stimulation. In summary, these findings provide a foundation for future investigations of the molecular classification and evolutionary patterns of Toll-like receptors in invertebrates, and the innate immune responses of TLR signaling pathways in Mollusca. Graphical abstract: Image 1 Highlights: P-TLR, V-TLR, Ls-TLR and sP-TLR genes were identified and characterized from Ruditapes philippinarum transcriptome . The four families of molluscan TLRs underwent positive selection, and PSSs of them are located in different domain. RpTLRs dominantly exist in hemocytes and significantly up-regulated by Vibrio anguillarum stimulation.